2007
DOI: 10.4049/jimmunol.179.7.4635
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Regulates the Duration of TCR Engagement Needed for Commitment to Effector Function

Abstract: In naive T cells, engagement of the TCR with agonist peptide:MHC molecules leads to phosphorylation of key intracellular signaling intermediates within seconds and this peaks within minutes. However, the cell does not commit to proliferation and IL-2 cytokine production unless receptor contact is sustained for several hours. The biochemical basis for this transition to full activation may underlie how T cells receive survival signals while maintaining tolerance, and is currently not well understood. We show he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
77
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 71 publications
8
77
0
2
Order By: Relevance
“…Conversely, sustained Lck activation can result in a loss of tolerance and the onset of disease (3,74). We propose that elevated TCR-induced SFK activation in TCPTP-deficient T cells may be responsible for the inflammatory and autoimmune phenotype in Lck-Cre;Ptpn2 fl/fl mice.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, sustained Lck activation can result in a loss of tolerance and the onset of disease (3,74). We propose that elevated TCR-induced SFK activation in TCPTP-deficient T cells may be responsible for the inflammatory and autoimmune phenotype in Lck-Cre;Ptpn2 fl/fl mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence suggested that this kinase also generates negative signals that downregulate T cell and MC activation. For example, treatment of BMMCs with the specific Fyn inhibitor SU6656 or small interfering RNAmediated knockdown of Fyn leads to increased phosphorylation of AMPK, its upstream kinase LKB1, and its downstream target acetyl-CoA carboxylase in the absence of FcεRI stimulation (59), and Fyn negatively regulates TCR signaling in CD8 T cells (60). Our data add to the notion that Fyn kinase acts as a negative modulator of specific immune responses, limiting, in our particular case, the amount of TLR4-triggered TNF.…”
Section: Discussionmentioning
confidence: 99%
“…2). However, Fyn is also involved in feedback inhibition of TCR signaling through phosphorylation of the transmembrane adapter phosphoprotein associated with glycosphingolipid-enriched domains that recruits Csk and results in phosphorylation and inhibition of Lck function (45). Feedback inhibition of TCR signaling by Fyn is implicated in the induction of T cell anergy (46,47), and it is possible that MAPK-dependent inhibition of rpS6 Ser 240/4 phosphorylation also has important functional consequences.…”
Section: Discussionmentioning
confidence: 99%